Parenting Patterns and Family Characteristics among Stunted Toddlers in Palembang - Sari, Indah Purnama; Ardillah, Yustini; Yuliarti, Yuliarti (Universitas Airlangga, 2022)
Until today, there are still more than 20% children under five years old experiencing stunting due to malnutrition over a long time both in Indonesia and also globally. Therefore, an integrated program is needed to reduce the prevalence of stunting. This study investigated the correlation between parenting patterns and family characteristics with stunting. A matched case-control design was used based on age. Up to 40 cases and 40 controls of mothers having toddlers aged 24-59 months were selected as samples using simple random sampling technique. This study was conducted in Seberang Ulu I Sub-District, Palembang City, from September to October 2020. The data that has been collected were analyzed using univariate and bivariate analysis. The result showed that stunted and normal toddlers were mostly from mothers with poor parenting patterns in terms of feeding (72.5% & 45.0%), hygiene and sanitation (35.0% & 32.5%), and health care (42.5% & 15.0%). In addition, more cases of stunting came from mothers with high school education and below, low-income, at least 4 family members, and having more than 1 toddler. Feeding pattern, health care pattern, and mother's education affect toddlers' growth. The risk of stunting was higher in toddlers raised by mothers with low education, with poor feeding and health care practices than else.